Critical investigation of the impact of brand communities and new media in marketing Sony’s PlayStation - santhosh, Sanjith (2010)
The gaming industry has flourished in the recent years. It is interesting to see many gaming companies competing against each other to attain the top spot in the gaming industry. The companies have resorted to invest a lot in understanding consumer behavior to gain maximum benefit for both the firm in terms of sales and consumer in terms of gaming experience. Companies have identified that brand community and new media as the best medium to interact with its loyal customers. This research critically examines these interactions between consumer and the company and tries to gain insights on the impact of marketing strategies used by Sony to market its Sony PlayStation. It also identifies if the strategies implemented by Sony are effective. And in order to achieve this, both the company and consumer point of view was observed from new media techniques and brand communities. Even though a lot of marketing strategies used by Sony was effective, it was found that the consumer’s perception about the reliable source of information was not available from the official forums.